Genetic diversity analysis among soybean (Glycine max) genotypes based on agro morphological characters - SAREO, HORMICHON; DEVI, H NANITA; DEVI, T SUNANDA; KARAM, NILIMA; DEVI, L SOPHIA (The Indian Journal of Agricultural Sciences, 2018)
The experiment was carried out to study the extent of genetic diversity among the 75 genotypes of soybean [Glycine max (L.) Merr.] under rainfed condition of Manipur by employing Mahalanobis DÂ² analysis based on 13 morphological characters. The 75 genotypes of soybean were grouped into 9 clusters. Maximum numbers of genotypes were included in the cluster I comprising 28 genotypes followed by cluster II with 13 genotypes, cluster IV with 12 genotypes, cluster III and cluster V with 9 genotypes each and clusters VI, VII, VIII and IX with 1 genotype each. The value of intra-cluster distances ranged from 0.00 to 1181. The highest inter cluster distance (8937) was observed between cluster III and IX. The character plant height (34.13%) contributed highest to the total divergence of the genotypes, followed by pods/plant (29.62%) and days to 80% maturity (14.59%). The highest cluster means values for yield and its component characters were observed in cluster IX. On the basis of inter-cluster distance, cluster mean values, mean per se performance it is advisable to attempt crosses between genotypes from cluster III and cluster IX which may lead to obtaining higher heterotic effect and broad spectrum variability in the segregants.